Random Ising model in three dimensions: theory, experiment and simulation – a difficult coexistence - Berche, B.; Berche, P.E.; Chatelain, C.; Janke, W. (Condensed Matter Physics, 2005)
We discuss different approaches to the study of the effect of disorder in the three-dimensional Ising model. From the theoretical point of view, renormalization group calculations provide quite accurate results. Experiments carried out on crystalline mixtures of compounds lead to measurements as accurate as three digits on the values of critical exponents. Numerically, extensive Monte Carlo simulations then pretend to be of comparable accuracy. Life becomes complicated when details are compared between the three approaches. Ми обговорюємо різні підходи до вивчення впливу безладу в тривимірній моделі Ізинга. З теоретичної точки зору, обчислення за допомогою ренормалізаційної групи забезпечують досить добрі результати. Експерименти, виконані на кристалічних сумішах компонентів дають значення критичних показників з точністю до трьох значень після коми. Чисельно, великі Монте Карло симуляції також претендують на співмірну точність. Задача стає складнішою коли порівнювити деталі трьох підходів.